Pengaruh Pendapatan Asli Daerah (PAD) Dan Dana Perimbangan Terhadap Belanja Daerah Di Indonesia - Susanti Susanti; Sunarto Wage; Syahril Effendi (LPPM Universitas Putera Batam, 2023)
This research aims to analyze and find out how much influence regional original income (PAD) and balancing funds have on regional expenditure in Indonesia. Research data comes from the Central Statistics Agency in 34 Provinces in Indonesia for the period 2018 - 2021 with 136 data. After data collection, there were several provinces in Indonesia whose data were incomplete so the data used was 100. The provinces with incomplete data were: Bengkulu, Bali, South Kalimantan, Central Kalimantan, West Nusa Tenggara, South Sulawesi, West Sulawesi, Main Maluku and West Papua. Data analysis techniques use (1) Classic assumption tests, namely normality, heteroscedasticity, multicollinearity and autocorrelation tests, (2) Multiple linear regression analysis, t test, F test and coefficient of determination. The results of the research show that partially original regional income has no effect on regional spending in Indonesia, balancing funds have no effect on regional spending in Indonesia, and simultaneously original regional income and balancing funds have no effect on regional spending in Indonesia.